2020
DOI: 10.7759/cureus.9300
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars as a Future, Promising Solution for Financial Toxicity: A Review with Emphasis on Bevacizumab

Abstract: A biosimilar is a biochemical product like another already approved biologic agent, known as the reference agent. To be endorsed by the Food and Drug Administration (FDA), biosimilars must demonstrate that they are as safe and effective as their reference item, with no clinical distinction. Humanized monoclonal antibodies (mAb) are revolutionizing the treatment of gastrointestinal and gynecologic malignancies. Bevacizumab, trastuzumab, cetuximab, rituximab, and pegfilgrastim are the most widely used mAb produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Compared with conventional therapies, the costs of therapeutic mAbs and fusion proteins are very high, which may restrict the access of patients to optimal therapy for many serious diseases. One of the major drivers of high costs is the lack of sufficient competition in the biologicals market, especially among products that have lost patent and data protection [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional therapies, the costs of therapeutic mAbs and fusion proteins are very high, which may restrict the access of patients to optimal therapy for many serious diseases. One of the major drivers of high costs is the lack of sufficient competition in the biologicals market, especially among products that have lost patent and data protection [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, bevacizumab was also approved as a treatment for glioblastoma multiforme (GBM) and renal cell carcinoma as a second-line treatment. Since then, several randomized clinical trials have shown that it improves survival, making it one of the most widely used oncologic drugs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs reported in these cases include amoxicillin/clavulanate and piperacillin/tazobactam (first patient), azithromycin (second patient), lopinavir (third patient), oseltamivir, lopinavir/ritonavir, azithromycin, ceftriaxone and piperacillin/tazobactam (fourth patient) and piperacillin/tazobactam, azithromycin and ceftriaxone (fifth case). These drugs could potentially have contributed to the development of HA in these patients, as already reported in literature [ 22 25 ]. However, there are no reported cases in which the use of these drugs may have triggered HA in patients with G6PDD.…”
Section: Discussionmentioning
confidence: 61%